Antibacterial Activity of an Anodized TiNbSn Alloy Prepared in Sodium Tartrate Electrolyte - Kurishima, Hiroaki; Mori, Yu; Ishii, Keiko; Inoue, Hiroyuki; Mokudai, Takayuki; Fujimori, Satoko; Itoi, Eiji; Hanada, Shuji; Masahashi, Naoya; Aizawa, Toshimi (Frontiers in Bioengineering and Biotechnology, 2022)
In this study, we anodized a TiNbSn alloy with low Young’s modulus in an electrolyte of sodium tartrate with and without hydrogen peroxide (H2O2). The photo-induced characteristics of the anodized alloy were analyzed for crystallinity and electrochemical conditions with comparisons to the effect with the addition of H2O2. The antibacterial activity was evaluated using methicillin-resistant Staphylococcus aureus and other pathogenic bacteria according to ISO 27447, and time decay antibacterial tests were also conducted. The anodized oxide had a porous microstructure with anatase- and rutile-structured titanium dioxide (TiO2). In contrast, the peaks of rutile-structured TiO2 were accelerated in the anodized TiNbSn alloy with H2O2. The formation of hydroxyl radicals and methylene blue breaching performance under ultraviolet irradiation was confirmed in the anodic oxide on TiNbSn alloy with and without H2O2. The anodic oxide on TiNbSn alloy had a robust antibacterial activity, and no significant difference was detected with or without H2O2. We conclude that anodized TiNbSn alloy with sodium tartrate electrolyte may be a functional biomaterial with a low Young’s modulus and an antibacterial function.